2020
DOI: 10.3390/ijms21176342
|View full text |Cite
|
Sign up to set email alerts
|

Genomics and Functional Genomics of Malignant Pleural Mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is a rare, aggressive cancer of the mesothelial cells lining the pleural surface of the chest wall and lung. The etiology of MPM is strongly associated with prior exposure to asbestos fibers, and the median survival rate of the diagnosed patients is approximately one year. Despite the latest advancements in surgical techniques and systemic therapies, currently available treatment modalities of MPM fail to provide long-term survival. The increasing incidence of MPM highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 203 publications
(261 reference statements)
1
25
0
Order By: Relevance
“…Therefore, since the bacterial flora involved in the onset of mesothelioma has been identified, it may be possible to prevent the onset of mesothelioma in future clinical applications by controlling these two species. In particular, asbestos inhalation is a known cause of mesothelioma, and the prevention of mesothelioma is particularly important in high-risk populations exposed to asbestos [ 10 ]. The establishment of a probiosis model, with antimicrobial or vaccine therapy targeting the two target species identified in this study, may serve as a treatment regime for the prevention of the onset of mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, since the bacterial flora involved in the onset of mesothelioma has been identified, it may be possible to prevent the onset of mesothelioma in future clinical applications by controlling these two species. In particular, asbestos inhalation is a known cause of mesothelioma, and the prevention of mesothelioma is particularly important in high-risk populations exposed to asbestos [ 10 ]. The establishment of a probiosis model, with antimicrobial or vaccine therapy targeting the two target species identified in this study, may serve as a treatment regime for the prevention of the onset of mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologically, mesothelioma is strongly correlated with asbestos inhalation and, since its onset, is usually observed approximately 40 years after asbestos inhalation. As of 2020, it is being increasingly reported worldwide [ 10 ]. Therefore, there is an urgent need to clarify its pathophysiology and establish methods for preventing its onset, as well as to introduce new treatments [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…They maintained the same characteristics during several passages in vivo as well as the doubling time that remained stable from the second passage on. They represent, therefore, a good proxy to study new possible interventions and new targeted therapies on the basis of available evidence arising from the molecular characterization of MPM tumors [ 12 , 13 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the standard combination of cisplatin and pemetrexed chemotherapy agents [ 6 ] prolongs the median survival time by approximately 3 months only [ 7 ]. In the last years, genetic studies on MPM reported a low prevalence of oncogene driver mutations and low tumor mutational burden, but frequent copy-number losses and recurrent somatic mutations in oncosuppressor genes such as BAP1, NF2, and CDKN2A [ 8 , 9 , 10 , 11 , 12 , 13 ]. Unfortunately, no targeted therapies exploiting these alterations have emerged.…”
Section: Introductionmentioning
confidence: 99%